Innovations in mass timber lateral systems - Bailey, Dawson (Kansas State University, 2022)
As mass timber becomes increasingly popular in the United States and around the world, there comes more demand for mass timber in larger buildings. With this demand comes a necessity for these buildings to be able to withstand seismic forces; and in some locations, these forces can get quite high. Typical mass timber lateral systems (such as CLT shear walls) have worked fine for lower seismic forces and shorter buildings, but with this new demand comes a need for newer systems. Rocking timber walls is one of these systems. The goal of a rocking timber wall is to allow the lateral wall system to move in the case of high seismic force, thus reducing the loading the wall experiences. This is done with vertical post tensioning (PT) within cross-laminated timber panels (CLT). In addition, easily replaceable energy dissipation devices, such as U-shaped flexural plates (UFPs), allow for concentration of inelastic deformation during rocking of the walls, which keeps the CLT and PT components free from harm. Another system used to handle seismic load in tall mass timber structures are inter-story isolation systems. These systems can isolate the force at separate levels, effectively decreasing the load the foundation takes from the building's movement. Even newer than these systems is the Floor Isolated Re-centering Modular Construction System (FIRMOC), which utilizes rocking timber walls, inter-story isolation, and the addition of prefabricated modular mass timber to create a system capable of effectively and efficiently dealing with large seismic forces. This report seeks to present these innovative, capable, and effective lateral systems for seismic forces in large scale mass timber structures in a manner that provides understanding of how they work and what makes them effective.
Keywords: Mass timber; Lateral system; Rocking timber walls